Determination of sampling time interval for investigating ecological trends of tintinnids. (2nd June 2022) - Baek, Sang-Soo; Kim, Young Ok; Choi, Jungmin; Cho, Hong Yeon; Jang, Min-Chul
Abstract: Tintinnids are a major group of planktonic ciliates. To determine a desirable sampling interval for analyzing the temporal dynamics of tintinnids, intensive monitoring was conducted on the southern coast of Korea. The mean sampling interval was 1.5 days. The abundance of tintinnids were analyzed by microscopy. The high- frequency temporal pattern showed detailed changes in concentrations and a distinct seasonality in the abundance of tintinnids. An optimal monitoring interval for tintinnid abundance estimations was determined by polynomial interpolation and statistical analysis, involving three steps, namely, interpolation by increasing the number of sampling intervals, graphical analysis with interpolated data and determination of the changepoint depending on the interpolated results. The value of changepoint was 7 days, indicating the optimal monitoring interval. Therefore, data collection at weekly intervals is sufficient and desirable for tracing the temporal signals of tintinnid ecology and its long-term trends.